Reverse photoluminescence responses of Ln(iii) complexes to methanol vapor clarify the differentiated energy transfer pathway and potential for methanol detection and encryption. Issue 47 (9th November 2020) - Yin, Shao-Yun; Fu, Peng-Yan; Pan, Mei; Guo, Jing; Fan, Ya-Nan; Su, Cheng-Yong
Abstract : A VOC detection and optical encryption model based on the uncommon reverse photoluminescence response of isomorphic Eu(iii ) and Tb(iii ) complexes to MeOH vapor. Abstract : Advanced photoluminescent (PL) materials with unique and unclonable photophysical behaviors are important for potential applications in hazardous material detection and optical encryption. We herein present new detecting and encrypting models based on the uncommon reverse photoluminescence response of Eu(iii ) and Tb(iii ) complexes with isomorphic structures. Upon the stimulus of methanol vapor, the characteristic red emission of Eu(iii ) shows an unusual turn on magnification depending on crystal morphologies, manifesting a more sensitive response from the lamellar crystals with not so perfect crystalline forms, while the green emission of Tb(iii ) turns down conversely. This clarifies an unprecedent proof for the differentiated energy transfer (ET) pathway, i.e., triplet ET to Eu(iii ), while singlet ET to Tb(iii ) in lanthanide complexes. Furthermore, patterned taggants can be designed from the interweaving of unary and binary Eu/Tb(iii ) complexes, presenting new optical detecting and encrypting models with pixel-selective responding and methanol vapor detecting capacities.